Formulating the success of citizen participation in urban regeneration: Insights and perplexities from Lisbon - Falanga, Roberto (2019)
Worldwide, participatory processes have expanded by covering a wide range of policy areas, including urban regeneration. Acknowledging the formulation of success as the first methodological step for the evaluation of participatory processes, the article discusses insights and perplexities emerging from the BipZip Programme in Lisbon. The proposal of an alternative agenda builds on the need to provide the formulation of success with information on the macro, meso andmicro contexts, to be collected through the participation of local partners and political/administrative agents. Theoretical and empirical knowledge concur to the international debate on the evaluation of citizen participation in urban regeneration.